2013
DOI: 10.3126/ajms.v4i2.8031
|View full text |Cite
|
Sign up to set email alerts
|

Students’ views on audio visual aids used during didactic lectures in a medical college

Abstract: Introduction: Medical teachers have conventionally been using different teaching methods to educate medical students previously dominated by blackboard and slide projectors. Now day's audiovisual aids such as power point have been used. The optimum use of audiovisual aids is essential forderiving their benefits. This study was done to know the students' preference regarding the various audiovisual aids, with an aim to improve their use in didactic lectures. Material &Methods: Two hundred and eighty six from fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
1
10
0
2
Order By: Relevance
“…Our finding is parallel to a study done by Banerjee I et al; [7] , Kumar A et al; [8] in India also reported that combination of teaching aids is the best method of teaching and learning methodology. Thus the reason for combinations approach is, it might help the students to be alert and to make them actively involved during class.…”
Section: Resultssupporting
confidence: 90%
“…Our finding is parallel to a study done by Banerjee I et al; [7] , Kumar A et al; [8] in India also reported that combination of teaching aids is the best method of teaching and learning methodology. Thus the reason for combinations approach is, it might help the students to be alert and to make them actively involved during class.…”
Section: Resultssupporting
confidence: 90%
“…n = 142 (94.67%) students [Table/ Fig-6] accepted that their use inspired them for in-depth reading of subject. Review of literature [13,14] also supports the use of audio visual aids in medical colleges. These aids provide a three dimensional view of medical diagrams and clinical images that helps the students in perceiving them correctly.…”
Section: Resultsmentioning
confidence: 88%
“…Similarly, a study done by Giri PA et al [10] found that use of a combination of audiovisual aids was more appreciated by the undergraduate medical students. Another study done by Kumar A et al [11] also found that 50.0% students showed a preference for the use of a combination of audio-visual aids during the lecture delivery. A study by Mohan L et al [9] also found consistent results with our study-reporting majority of students in their study group preferred mixed A-V aids especially for understanding a particular topic.…”
Section: Discussionmentioning
confidence: 89%